2010
DOI: 10.1186/1756-0500-3-330
|View full text |Cite
|
Sign up to set email alerts
|

Relevance of the light signaling machinery for cellulase expression in trichoderma reesei (hypocrea jecorina)

Abstract: BackgroundIn nature, light is one of the most important environmental cues that fungi perceive and interpret. It is known not only to influence growth and conidiation, but also cellulase gene expression. We therefore studied the relevance of the main components of the light perception machinery of Trichoderma reesei (Hypocrea jecorina), ENV1, BLR1 and BLR2, for production of plant cell wall degrading enzymes in fermentations aimed at efficient biosynthesis of enzyme mixtures for biofuel production.FindingsOur … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 41 publications
2
25
0
Order By: Relevance
“…Surprisingly, while also in N. crassa WC-1, WC-2 and VVD exert a positive effect on transcription of the major cellulase gene, the cellulase mixture secreted into the culture medium by mutants in the respective genes was even more efficient than that in the wild-type (Schmoll et al, 2011, ms submitted). A similar effect was recently also observed in T. reesei (Gyalai-Korpos et al, 2010). In both cases, the light response machinery was suggested to accomplish this enhancement of cellulase activity despite decreased transcription of cbh1 (or its orthologue) by alteration of the composition of the secreted enzyme mixture for higher efficiency dependent on light.…”
Section: Light-dependent Modulation Of Cellulase Gene Expression Is Amentioning
confidence: 48%
See 1 more Smart Citation
“…Surprisingly, while also in N. crassa WC-1, WC-2 and VVD exert a positive effect on transcription of the major cellulase gene, the cellulase mixture secreted into the culture medium by mutants in the respective genes was even more efficient than that in the wild-type (Schmoll et al, 2011, ms submitted). A similar effect was recently also observed in T. reesei (Gyalai-Korpos et al, 2010). In both cases, the light response machinery was suggested to accomplish this enhancement of cellulase activity despite decreased transcription of cbh1 (or its orthologue) by alteration of the composition of the secreted enzyme mixture for higher efficiency dependent on light.…”
Section: Light-dependent Modulation Of Cellulase Gene Expression Is Amentioning
confidence: 48%
“…Also recent findings on the functions of the COP9 signalosome in A. nidulans, which is a crucial regulator of ubiquitin ligases Nahlik et al, 2010) open up excitingly new topics for investigation of cell signalling with the involvement of protein modification. Additionally, the recently described mechanisms of regulation of mRNA stability by decapping (Morozov et al, 2010) may also play a role in posttranscriptional regulation of cellulase gene expression in T. reesei (Gyalai-Korpos et al, 2010). On the other hand, studies on signal transduction pathways and especially light response in recent years, clearly showed that light is an important environmental cue, which cannot be neglected when analyzing T. reesei.…”
Section: Perspectives and Challengesmentioning
confidence: 99%
“…Transcriptional analysis of deletion mutants under light and dark conditions showed that photoreceptor regulation of carbon metabolism is mediated by BLR1 and BLR2 stimulation of env1 transcription in T. reesei, whereas in N. crassa VIVID had a negative effect on the WCC [27]. Also, BLR1 and BLR2 in T. reesei are not considered to act as a complex under darkness [98]. The T. reesei ENVOY protein has an additional function; it affects the expression of G-protein alpha subunits GNA1 and GNA3.…”
Section: Light Regulation Of Cazyme-encoding Gene Expressionmentioning
confidence: 99%
“…In T. reesei, the homologues of WC-1, WC-2 and VIVID, which are BLR1, BLR2 and ENV (ENVOY) affect CAZyme-encoding gene expression. In darkness, deletion of some of these genes increased the cellulase activity in the culture filtrate [98]. Gyalai-Korpos et al [98] considered that the effect on cellulase activity of blr1 and blr2 deletion was due to differences in protein secretion and that of env1 deletion due to adjustments in response to the environment.…”
Section: Light Regulation Of Cazyme-encoding Gene Expressionmentioning
confidence: 99%
See 1 more Smart Citation